2002
DOI: 10.1038/ng870
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cis-acting factors in replication-mediated trinucleotide repeat instability in primate cells

Abstract: The mechanism of disease-associated trinucleotide repeat instability involves cis-acting factors (cis-elements) in the vicinity of the repeat, but the nature of these elements is unknown. One cis-element may be the location of the replication origin relative to the repeat. We have used an SV40 DNA replication system to investigate the effect of the loca-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
193
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 49 publications
5
193
1
Order By: Relevance
“…The process of instability is likely to involve DNA slipped/secondary structures (out-of-register interstrand mispairings at repeat sequences). One hypothesis predicts that expansion events arise from errors at DNA replication forks (10,11). We have shown that cis-elements such as the location of replication initiation and fork direction, relative to a repeat tract, can lead to different types and frequencies of repeat instability (10).…”
mentioning
confidence: 95%
“…The process of instability is likely to involve DNA slipped/secondary structures (out-of-register interstrand mispairings at repeat sequences). One hypothesis predicts that expansion events arise from errors at DNA replication forks (10,11). We have shown that cis-elements such as the location of replication initiation and fork direction, relative to a repeat tract, can lead to different types and frequencies of repeat instability (10).…”
mentioning
confidence: 95%
“…The work by Cleary et al 2 helps to explain the nature of the cis-factors that are potentially responsible for TNR expansion. In so doing, the authors developed the first experimental system for measuring TNR expansions in mammalian cells.…”
Section: Location Location Locationmentioning
confidence: 99%
“…Two previous observations made in bacteria and yeast were confirmed: only repeats of premutational lengths were unstable, and expansions were only observed in one orientation of a repeat relative to the replication origin. Cleary et al 2 suggest that the formation of hairpins within the (CTG) ncontaining Okazaki fragment is responsible for the repeat's expansion (Fig. 1).…”
Section: Location Location Locationmentioning
confidence: 99%
See 2 more Smart Citations